Comprehensive Analysis of Eleutherococcus senticosus (Rupr. & Maxim.) Maxim. Leaves Based on UPLC-MS/MS: Separation and Rapid Qualitative and Quantitative Analysis - Hu, Jianping; Wu, Dan; Sun, Yanping; Zhao, Hongquan; Wang, Yangyang; Zhang, Wensen; Su, Fazhi; Yang, Bingyou; Wang, Qiuhong; Kuang, Haixue (Frontiers in Pharmacology, 2022)
Eleutherococcus senticosus (Rupr. & Maxim.) Maxim leaves (ESL) have long been a favorite with people as a natural edible green vegetable, in which phenols and saponins are the main characteristic and bioactive components. This study was first carried out to comprehensively analyze the phenols and saponins in ESL, including phytochemical, qualitative, quantitative and bioactivity analysis. The results showed that 30 compounds, including 20 phenolic compounds and 7 saponins, were identified. 12 of them were isolated from Eleutherococcus Maxim. for the first time. In the qualitative analysis, 30 phenolic compounds and 28 saponins were accurately detected and their characteristic cleavage processes were described by UPLC-QTOF-MS/MS. 10 representative ingredients were quantitated in 29 different regions via a 4000 QTRAP triple quadrupole tandem mass spectrometer (UPLC-QTRAP-MS/MS), and it was found that S19 (69.89±1.098 mg/g) and S1 (74.28±0.733 mg/g) had the highest contents of total phenols and saponins, respectively. The newly developed analysis method for the quantitative determination was validated for linearity, precision, and limits of detection and quantification, which could be applied to the quality assessment of ESL. In vitro experiment, the α-glucosidase inhibitory effect of phenolic fraction was higher than others, indicating that the phenolic content may be related to the hypoglycemic activity. It was also suggested that ESL could be developed as a natural potential effective drug or functional food.